Life table and demographic parameters of the metallic blue ladybeetle, Curinus coeruleus mulsant, fed with the Asian citrus psyllid, Diaphorina citri Kuwayama - Soemargono, Albertus; Ibrahim, Yusof; Ibrahim, Rohani; Osman, Mohammad Shamsudin (Universiti Putra Malaysia Press, 2008)
Life table parameters were calculated for the blue metallic ladybeetle, Curinus coeruleus Mulsant, fed with the Asian citrus psyllid, Diaphorina citri Kuwayama, at temperatures of 26 - 28° and 75 - 85% RH and natural photoperiod in the insectary of Faculty of Agriculture, Universiti Putra Malaysia. The development of immature stages took 19.1± 0.3 days; mated adult females lived for 34.2 ± 4.7 (range 24-39) days and produced a mean of 80.3 ± 13.6 progeny female-1 during oviposition period of 21.3 ± 1.4 days, with a sex ratio of 1:1.8 (:). The net reproductive rate (R0) was 59.1 and the capacity for increase (rc) was 0.113. The finite rate of increase (λ) was 1.29 female-1 day-1 while the intrinsic rate of natural increase (rm) was 0.116 female-1 day-1. Each female contributed 60.2 individuals to the population in a mean generation time (T) of 35.3 days.